(untitled) (Economics and region, 2025)
This article examines the wartime challenges to transfer pricing control in Ukraine and analyzes new tax avoidance schemes that became widespread during 2022–2024. The full-scale war has created unprecedented risks and uncertainty for both taxpayers and fiscal authorities, disrupting regular international trade and limiting the ability to perform traditional audits. These conditions have amplified risks of tax base erosion and prompted the emergence of novel abuse strategies. Four key types of abuse that intensified under martial law are identified and analyzed: (1) fictitious transactions and documentation with related parties, often involving artificial losses or penalties to shift profits abroad; (2) misuse of humanitarian and donor aid mechanisms to disguise commercial imports or offshore capital transfers; (3) pseudo-sponsorship (donor) support from non-resident affiliates masquerading as non-taxable grants, while effectively acting as reverse thin capitalization; and (4) pseudo-payments to shell companies in low-tax jurisdictions under the guise of consultancy or service fees. The paper discusses the economic instability that led to a significant decline in the volume of controlled transactions and the operational difficulties faced by tax authorities in verifying the reality and purpose of cross-border transfers. Based on the findings, the article proposes a set of strategic directions for enhancing the effectiveness of transfer pricing control mechanisms both during wartime and throughout the post-war recovery period. These include the development and broader implementation of automated risk assessment systems, the expansion of analytical tools for detecting atypical pricing patterns, and the integration of tax, customs, and financial databases. Special emphasis is placed on deepening international cooperation by enhancing the practical use of exchanged tax information, improving real-time data integration, and actively engaging in global initiatives such as the OECD’s BEPS framework to counter cross-border tax avoidance more effectively. The restoration of full-scope transfer pricing audits is considered essential for rebuilding regulatory capacity, while increased transparency and traceability of financial flows are identified as critical to safeguarding fiscal sustainability and minimizing profit-shifting risks under crisis conditions.